Granularity in granular cell ameloblastoma - Andamuthu Yamunadevi (Journal of Pharmacy and Bioallied Sciences, 2014)
Granular cell ameloblastoma (GCA) is one of the rare histological variants of ameloblastoma (1.5-3.5%), identified by Krompechner in 1918 and is diagnosed by the characteristic presence of granular cells. These granular cells are seen in several physiological and pathological conditions and the granularity in GCA is due to lysosomal aggregates. This review is about the clinical features, histopathological features and differential diagnosis of GCA and also adds the theories for occurrence of granularity, electron microscopic findings, cell signaling pathways and immunohistochemistry findings related to these granular cells in GCA.